2005
DOI: 10.1139/x05-050
|View full text |Cite
|
Sign up to set email alerts
|

Fire history and forest age distribution of an unmanaged Picea abies dominated landscape

Abstract: We examined fire history and forest age distribution in an unmanaged, Picea-dominated landscape in the Paanajärvi wilderness, located in northeastern Fennoscandia and northwest Russia. Maximum tree age was determined in 61 systematically located study plots in an area of about 6600 ha. Fire scars were examined in living and dead trees in the study plots and elsewhere in the study area. Charcoal and pollen analyses of peat were performed on samples from two locations. Fires had been rare in the landscape. Nearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 43 publications
1
62
0
1
Order By: Relevance
“…Other research has indicated that changes in human influence have resulted in changes in fire regimes. The results of a study by Wallenius et al (2005) revealed the non-random spatial and temporal nature of forest fires in an unmanaged area of Fennoscandia and northwest Russia, suggesting that much of the historical fire activity in this area was human-caused, and that a change in human behaviour had resulted in a change in fire regime in this area (in contrast to other theories that climate change or a change in fire suppression activity were causal agents of changes in fire regimes).…”
Section: Natural Disturbancesmentioning
confidence: 89%
“…Other research has indicated that changes in human influence have resulted in changes in fire regimes. The results of a study by Wallenius et al (2005) revealed the non-random spatial and temporal nature of forest fires in an unmanaged area of Fennoscandia and northwest Russia, suggesting that much of the historical fire activity in this area was human-caused, and that a change in human behaviour had resulted in a change in fire regime in this area (in contrast to other theories that climate change or a change in fire suppression activity were causal agents of changes in fire regimes).…”
Section: Natural Disturbancesmentioning
confidence: 89%
“…We visually cross-dated the tree-ring series (Yamaguchi 1991), using master chronologies from northern Fennoscandia (Aakala et al 2009;Wallenius et al 2010), and verified measurement quality statistically, using the COFECHA-program (Holmes 1983). Since P. abies-dominated boreal forest stands are prone to severe forest fires, we assumed the oldest verified tree age within a stand to represent the minimum time since the last stand-replacing fire (Wallenius et al 2005). We added five years to the year of the innermost ring, as a conservative estimate of the time it takes to reach the sampling height.…”
Section: Data Analysesmentioning
confidence: 99%
“…Therefore, the human impact is the most plausible factor behind this pattern. Boreal forests were actively used for slash and burn agriculture for centuries in eastern Fennoscandia (Heikinheimo 1915;Taavitsainen et al 1998;Orrman 2003;Chernyakova 2014b) which could led to the increased fire frequency in the forest landscape (Zackrisson 1977;Lehtonen et al 1996;Lehtonen and Kolström 2000;Pitkänen et al 2002;Wallenius et al 2005). In addition to slash and burn agriculture, the other modes of human activity can increase the frequency of unintended fires in the forests near the villages.…”
Section: Large Scale Patterns In the Landscapementioning
confidence: 99%
“…Heath forests of southern boreal zone were largely affected by slash and burn agriculture (Heikinheimo 1915), and even in the mid boreal zone, the use of fire in agriculture has increased the fire frequency in the forest landscape (Zackrisson 1977;Lehtonen et al 1996;Lehtonen and Kolström 2000;Pitkänen et al 2002;Wallenius et al 2005). The extremely high fire frequency of the 19th century was followed by the current very low fire frequency because of the end of slash and burn agriculture and active fire prevention which is still carried out (Pitkänen et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation